Body fluid concentrations of bisphenol A and their association with in vitro fertilization outcomes. (27th May 2021) - Kim, Hyun-Ki; Ko, Dae-Hyun; Lee, Woochang; Kim, Kwang-Rae; Chun, Sail; Song, Junghan; Min, Won-Ki
Abstract: Bisphenol A (BPA) is an endocrine-disrupting chemical thought to mimic the action of oestrogens. There have been reports suggesting an association between BPA exposure and infertility in humans. In this prospective cohort study, 146 couples undergoing in vitro fertilization (IVF) were recruited. Total BPA concentrations were measured in urine, plasma, follicular fluid and semen samples using LC-MS/MS. Pregnancy (serum β-HCG >1.2 mIU/mL) was observed in 67 (45.9%) out of 146 couples. The mean of urine BPA for all participants was 3.7 ng/mL. In the logistic regression models, BPA concentrations of body fluids (female/male urine, female/male plasma, follicular fluid, and semen) did not significantly affect the outcomes such as pregnancy, presence of good quality embryo, or the proportion of normally fertilized oocytes. In the multiple linear regression models, BPA concentrations of body fluids did not significantly affect the parameters such as number of retrieved oocytes, peak E2 level, sperm concentration, and sperm motility. In conclusion, BPA concentrations in body fluids were not significantly associated with IVF outcomes such as pregnancy, good quality embryo, normally fertilized oocytes, number of retrieved oocytes, peak E2 level, sperm concentration, and sperm motility. Therefore, we could not find the evidence that the non-occupational low-dose exposure to BPA affects IVF outcomes.